The frailty syndrome in institutionalized elderly persons - Fluetti,Marina Tadini (2018)
Abstract Objective: to analyze the relationship between the level of frailty and sociodemographic and health characteristics among elderly residents of a long-term care facility (LTCF) in Ribeirão Preto, São Paulo, Brazil. Method: this descriptive and cross-sectional study included 56 elderly persons living in a LTCF. Data were collected from April to June 2016. A questionnaire addressing sociodemographic and health profiles was used together with the Mini-Mental State Examination, the Tilburg Frailty Indicator, the Barthel Index, and the Geriatric Depression Scale (GDS-15). Descriptive statistics were applied. The normality of the continuous variables was tested using the Shapiro-Wilk test. Spearman’s correlation was used for the continuous variables with frailty as the dependent variable. Result: Most elderly individuals were female (57.1%); the average age was 77.77; and 35.7% were widowed. In terms of health, 55.4% presented cognitive deficit; 62.5% had depression symptoms; 75.0% were considered frail; 42.9% had suffered falls in the last 12 months; and the individuals scored an average of 68.30 in the Barthel Index. A positive correlation between the frailty score and the GDS-15 (r=0.538; p=0.00) was observed, while a negative correlation was found between frailty and the Barthel Index (r=-0.302; p=0.02). Conclusion: increased frailty among institutionalized elderly persons is correlated with the presence of depressive symptoms and inferior performance of basic activities of daily living. The results of the present study can support the planning of care provided to elderly individuals living in LTCFs and encourage broader assessments of these individuals.